Correction: On distance-based topological indices and co-indices of fractal-type molecular graphs and their respective graph entropies. - Mehar Ali Malik; Muhammad Imran; Muhammad Adeel (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0290047.].